X-ray and ion emission studies from subnanosecond laser-irradiated SiO2 aerogel foam targets. (10th August 2017) - Kaur, C.; Chaurasia, S.; Pisal, A.A.; Rossall, A.K.; Munda, D.S.; Venkateswara Rao, A.; Deo, M.N.
Abstract: In this experiment, a comparative study of ion and X-ray emission from both a SiO2 aerogel foam and a quartz target is performed. The experiment is performed using Nd:glass laser system operated at laser energy up to 15 J with a pulse duration of 500 ps with focusable intensity of 10 13 –10 14 W/cm 2 on target. X-ray fluxes in different spectral ranges (soft and hard) are measured by using X-ray diodes covered with Al filters of thickness 5 µm (0.9–1.56 keV) and 20 µm (3.4–16 keV). A 2.5 times enhancement in soft X-ray flux (0.9–1.56 keV) and a decrease of 1.8 times in hard X rays (3.4–16 keV) for 50 mg/cc SiO2 aerogel foam is observed compared with the solid quartz. A decrease in the flux of the K -shell line emission spectrum of soft X rays is noticed in the case of the foam targets. The high-resolution K -shell spectra (He-like) of Si ions in both the cases are analyzed for the determination of plasma parameters by comparing with FLYCHK simulations. The estimated plasma temperature and density are T c = 180 eV, n e = 7 × 10 20 cm −3 and T c = 190 eV, n e = 4 × 10 20 cm −3 for quartz and SiO2 aerogel foam, respectively. To measure the evolution of the plasma moving away from the targets, four identical ion collectors are placed at different angles (22.5, 30, 45, and 67.5°) from target normal. The angular distribution of the thermal ions are scaled as cos n θ with respect to target normal, where n = 3.8 and 4.8 for the foam and quartz, respectively. The experimental plasma volume measured from the ion collectors and shadowgraphy images are verified by a two-dimensional Eulerian radiative–hydrodynamic simulation (POLLUX code).